Junction depth & defect characterization with the use of EBIC - Phua, Poh Chin. (2008)
There are two objectives to be achieved in this work. Firstly, it is desirable to determine a new method of reconstructing the charge collection probability so as to extract the junction depth of the device. Secondly, it is also desirable to extract the defect location using the perpendicular p-n junction geometry.